Arthur's Christmas - Brown, Marc Tolon (Boston : Little, Brown, 1984)
Arthur puts a lot of time, effort, and thought into his special present for Santa Claus.
"An Atlantic Monthly Press book.".
Keywords: Santa Claus -- Fiction; Gifts -- Fiction; Christmas -- Fiction; Animals -- Fiction; Gifts -- Fiction; Christmas -- Fiction; Santa Claus -- Fiction; Animals -- Fiction